A randomised controlled trial. Shifting boundaries of doctors and physiotherapists in orthopaedic outpatient departments. Issue 10 (1st October 1999) - Daker-White, G; Carr, A J; Harvey, I; Woolhead, G; Bannister, G; Nelson, I; Kammerling, M
Abstract : OBJECTIVE: To evaluate the effectiveness and cost effectiveness of specially trained physiotherapists in the assessment and management of defined referrals to hospital orthopaedic departments. DESIGN: Randomised controlled trial. SETTING: Orthopaedic outpatient departments in two hospitals. SUBJECTS: 481 patients with musculoskeletal problems referred for specialist orthopaedic opinion. INTERVENTIONS: Initial assessment and management undertaken by post-Fellowship junior orthopaedic surgeons, or by specially trained physiotherapists working in an extended role (orthopaedic physiotherapy specialists). MAIN OUTCOME MEASURES: Patient centred measures of pain, functional disability and perceived handicap. RESULTS: A total of 654 patients were eligible to join the trial, 481 (73.6%) gave their consent to be randomised. The two arms (doctor n = 244, physiotherapist n = 237) were similar at baseline. Baseline and follow up questionnaires were completed by 383 patients (79.6%). The mean time to follow up was 5.6 months after randomisation, with similar distributions of intervals to follow up in both arms. The only outcome for which there was a statistically or clinically important difference between arms was in a measure of patient satisfaction, which favoured the physiotherapist arm. A cost minimisation analysis showed no significant differences in direct costs to the patient or NHS primary care costs. Direct hospital costs were lower (p < 0.00001) in the physiotherapist arm (mean cost per patient = 256 Pounds, n = 232), as they were less likely to order radiographs and to refer patients for orthopaedic surgery than were the junior doctors (mean cost per patient in arm = 498 Pounds, n = 238). CONCLUSIONS: On the basis of the patient centred outcomes measured in this randomised trial, orthopaedic physiotherapy specialists are as effective as post-Fellowship junior staff and clinical assistant orthopaedic surgeons in the initial assessment and management of new referrals to outpatient orthopaedic departments, and generate lower initial direct hospital costs.